1999
DOI: 10.1074/jbc.274.28.19661
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Lipid-derived Malondialdehyde with Collagen

Abstract: Malondialdehyde is a product of fatty acid oxidation (e.g. from low density lipoprotein) implicated in the damage of proteins such as collagen in the cardiovascular system (Chio, K. J., and Tappel, A. L. (1969) Biochemistry 8, 2821-2827). Its concentration is raised in diabetic subjects probably as a side effect of increased protein glycation. Collagen has enzyme-catalyzed cross-links formed between its individual molecules that are essential for maintaining the structure and flexibility of the collagen fiber.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 39 publications
3
45
0
2
Order By: Relevance
“…Since MDA has bifunctional aldehydic properties, it has the potential to crosslink collagen molecules and thereby stiffen the collagen fibers. 27 Accordingly, MDA has been proposed to be responsible for the increased arterial stiffening seen in diabetic patients. 28 However, in our study there was no significant difference between MDA-collagen type IV levels in lesions from diabetic patients compared to non-diabetic patients.…”
mentioning
confidence: 99%
“…Since MDA has bifunctional aldehydic properties, it has the potential to crosslink collagen molecules and thereby stiffen the collagen fibers. 27 Accordingly, MDA has been proposed to be responsible for the increased arterial stiffening seen in diabetic patients. 28 However, in our study there was no significant difference between MDA-collagen type IV levels in lesions from diabetic patients compared to non-diabetic patients.…”
mentioning
confidence: 99%
“…In addition, we determined levels of MDA, an end product of lipid peroxidation. Since MDA can react with sulfhydryl groups, and has the potential to crosslink proteins (Esterbauer et al, 1991), it can reduce or abolish important protein functions (Slatter et al, 1999). Our present study demonstrated that BB-induced hepatic MDA levels in the ZT18 group were lower than those in the ZT6 group (third step in BB-induced hepatotoxicity), suggesting that the circadian mechanism that produces the difference in severity of BB-induced hepatotoxicity occurs within the first three steps of BB-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies employing acid hydrolysis did not reveal a cross-link involving a single MDA molecule under pseudo-physiological conditions in vitro (16). Here, we report some success in an attempt to isolate an MDA cross-link using alkaline hydrolysis of MDA reacted with both BSA and collagen.…”
mentioning
confidence: 78%
“…When using radioactivity, the column fractions were counted using a LKB Wallac 1219 Rack Beta scintillation counter and radioactive peaks located in relation to standard amino acids as described earlier (16).…”
Section: Synthesis Of Malondialdehyde-[2-c 14 ]mentioning
confidence: 99%